Increasing Walking Speed to Achieve a Pre-training Endurance Shuttle Walk Time of 5-10 min May Improve Test Responsiveness in People With Chronic Obstructive Pulmonary Disease. Issue 4 (5th July 2021) - Hill, Kylie; Chao, Yan Ling; Cavalheri, Vinicius; Ng, L. W. Cindy; Wootton, Sally L.; McKeough, Zoe J.; Jenkins, Sue C.; Eastwood, Peter R.; Hillman, David R.; Jenkins, Christine; Cecins, Nola; Spencer, Lissa M.; et al.
Abstract : Participants with chronic obstructive pulmonary disease who report modest symptoms during the 6-min walk test or incremental shuttle walk test achieve a long pre-training endurance shuttle walk test time. In this situation, performing the test at a faster speed to achieve a pretraining test between 5 and10 min may enhance responsiveness. Abstract : Purpose: The endurance shuttle walk test (ESWT) was used to evaluate ground-based walking training in chronic obstructive pulmonary disease. During pre-training testing, those who walked 5-10 min on the first ESWT with minimal symptoms performed additional ESWTs at increasing speeds until they were at least moderately symptomatic and terminated the test between 5 and 10 min. This report compares participant characteristics and test responsiveness with participants grouped according to whether or not faster walking speeds were selected for the ESWT during pre-training testing. Methods: We conducted a retrospective analysis of data collected in the intervention group during a randomized controlled trial. The intervention was supervised ground-based walking training, performed two to three times/wk, for 8-10 wk. Prior to and immediately following completion of training, participants completed the 6-min walk test (6MWT), incremental shuttle walk test (ISWT), and ESWT. Results: Data were available on 77 participants (70 ± 9 yr, forced expiratory volume in the first second of expiration [FEV1 ] 43 ± 15 % predicted). For those whom a faster speed was selected during the pre-training ESWTs were characterized by milder dyspnea and leg fatigue on completion of the baseline 6MWT and ISWT ( P < .05 for all). On training completion, the change in ESWT was greater in those for whom a faster speed was selected (376 ± 344 sec vs 176 ± 274 sec; P = .017). Conclusions: Participants who report modest symptoms on completion of the pre-training 6MWT or ISWT may achieve a long pre-training ESWT time. In this situation, repeating the pre-training ESWT at a faster walking speed to achieve an exercise time between 5 and 10 min with moderate symptoms may be advantageous.